2020
DOI: 10.1111/jan.14272
|View full text |Cite
|
Sign up to set email alerts
|

Effect of eHealth cardiac rehabilitation on health outcomes of coronary heart disease patients: A systematic review and meta‐analysis

Abstract: Aims To evaluate the effects of eHealth cardiac rehabilitation (CR) on health outcomes of coronary heart disease patients and to identify programme design, which may lead to more effective health benefits. Design A systematic review and meta‐analysis following Cochrane Handbook for Systematic Reviews of Interventions. Data sources Medline, EMBASE, CLNAHL, Web of Science, Scopus, PsycINFO, Cochrane Central Register of Controlled Trails, PubMed and CNKI were searched over the period from 1806 to April 2019. Revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
101
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(118 citation statements)
references
References 59 publications
2
101
2
2
Order By: Relevance
“…In other studies, the effect of mHealth-based interventions on QoL was unclear. Some meta-analyses have reported that mHealth-based interventions did not improve QoL in cancer survivors [42,43], while another study reported improved QoL in patients with coronary heart disease [44]. Therefore, the long-term effect of mHealth interventions on QoL should be investigated further.…”
Section: Principal Findingsmentioning
confidence: 99%
“…In other studies, the effect of mHealth-based interventions on QoL was unclear. Some meta-analyses have reported that mHealth-based interventions did not improve QoL in cancer survivors [42,43], while another study reported improved QoL in patients with coronary heart disease [44]. Therefore, the long-term effect of mHealth interventions on QoL should be investigated further.…”
Section: Principal Findingsmentioning
confidence: 99%
“…Several articles show promising results when eHealth is being used in medical fields [ 2 - 11 ]. For instance, it has been shown that eHealth interventions help to improve medication adherence [ 4 ], glycemic control in diabetes patients [ 6 ], and self-care among heart failure patients as well as improve the outcomes of cardiac rehabilitation among coronary heart disease patients [ 7 , 8 ] and improve mental health [ 9 , 10 ]. Teleconsultation by general practitioners has been proven as an alternative to face-to-face consultations in certain situations [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…3 Early diagnosis and treatment of this condition are important for the prognosis of patients. 4 Coronary artery bypass grafting (CABG) is often used to treat coronary heart disease in the surgical department. CABG can effectively relieve the symptoms of angina pectoris, improve myocardial ischemia, avoid occurrence of myocardial infarction, and improve the quality of life.…”
Section: Introductionmentioning
confidence: 99%